Change in Responsible Consumer Behaviour Through Generations? - Zsuzsanna Marton; Ildikó Ernszt; Nora Rodek; Tivadar Máhr (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
In our accelerated world, in the era of over-consumption, decisions and choices have got more and more emphases than before. In spite of the fact, that conscious and responsible behaviour did not draw as much attention as it does nowadays, the whole society suffers the consequences of decisions independently from which generation can be blamed. However, the education for responsible behaviour has started and become more important than ever, the real change in the attitude and the approach to responsibility still needs a lot of time. The research conducted among Hungarian consumers aims to reveal the differences between the generations' consumer behaviour with special focus on the FMCG market. In the analysis of the factors influencing consumer decision-making, the corporate marketing communication as well as the environmental and social aspects get central role.
Keywords: M31; 330; responsible consumers; generations; consumer decision-making; corporate marketing communication